Шляхи підвищення ефективності теплопостачання побутово-промислових об’єктів - Мартиняк, Марта (Видавництво Львівської політехніки, 2013)
This article describes experimental studies of modes of heating the industrial objects in combination with heat pump to determine efficiency and reliability. Were conducted experimental studies of the heating system and its individual elements without heat pump and hot water system with heat pump DHP-R. Research showed that the boiler achieves its full heat output calculated if sufficient of coolant (water) that circulates through it, with the appropriate temperature. Otherwise, a decrease in heat transfer device which causes resulting decrease in air temperature in heated rooms. Also they showed that the increase of hot water discharge in the heating system causes not proportional, but only a partial increase of heat in the room. The study confirmed the feasibility of using heat pumps, in general, lead to energy savings without violating thermal comfort room.
Keywords: теплова помпа; контрольно-вимірювальні прилади; температурні режими; теплопостачання; газовий котел; опалювальний прилад